Sponge gourd variety Thar Tapish developed for hot arid climate - Verma, Ajay Kumar; Samadia, D K; Gurjar, P S; Ram, Hanuman (Indian Horticulture, 2022)
Sponge gourd (Luffa cylindrica L.) is much liked indigenous and cooking cucurbit vegetable. Thar Tapish is selection through hybridization breeding from combination of AHSG-4 x AHSG-16. It is recommended in 2018 by ICAR-CIAH, Bikaner for cultivation under hot arid climate. It is developed for marketable quality fruit yield (145.8 q/ha) under high temperature and abiotic stressed conditions. It took 50 days for first tender fruit harvest. Tender fruits ready in 7-9 days for harvesting and 95–145 g weight are found best for fresh market and dehydration (8.35 % dry product). Vines are medium in growth (2.52 m) with 4.82-5.33 branches.